1995
DOI: 10.1074/jbc.270.40.23352
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Unique Mechanism Mediating the Shear-dependent Binding of Soluble von Willebrand Factor to Platelets

Abstract: We have studied the mechanism of interaction between soluble von Willebrand factor (vWF), labeled with fluorescein isothiocyanate (FITC), and platelets exposed to shear in a cone-and-plate viscometer. A flow cytometer calibrated with fluorescent bead standards was used to calculate the number of molecules associated with each platelet in suspension. To validate the methods and reagents used, binding of the same labeled vWF was assessed in the presence of ristocetin or ␣-thrombin and found to be saturable, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
232
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(239 citation statements)
references
References 37 publications
7
232
0
Order By: Relevance
“…The multimeric form of VWF is disrupted in types 2A and 2B of VWD (Figures 2A and B), decreasing the function of VWF. Normally, upon endothelial injury VWF's A1 and A3 domains bind to collagen, and the resultant shear stress changes the conformation of VWF to allow VWF binding to platelet GPIbα 8. In this way VWF acts as a bridge to bind platelets to exposed collagen on injured endothelium, acting as a first responder in coagulation.…”
Section: Classification Of Von Willebrand Diseasementioning
confidence: 99%
“…The multimeric form of VWF is disrupted in types 2A and 2B of VWD (Figures 2A and B), decreasing the function of VWF. Normally, upon endothelial injury VWF's A1 and A3 domains bind to collagen, and the resultant shear stress changes the conformation of VWF to allow VWF binding to platelet GPIbα 8. In this way VWF acts as a bridge to bind platelets to exposed collagen on injured endothelium, acting as a first responder in coagulation.…”
Section: Classification Of Von Willebrand Diseasementioning
confidence: 99%
“…109 Interestingly, it has been shown that molecular confinement enhances the deformation of entangled polymers under squeeze flow, 110 a condition which models pulsatile blood flow. Similarly, there are a considerably number of reports 27,34,35,42,59,60,[111][112][113] citing haemodynamic shear stress as the primary facilitator of the proteolytic cleavage of large vWF multimers freshly released from endothelial cells as well as vWF-mediated platelet adhesion during haemostasis. The accumulation of large vWF multimers in the plasma may lead to disease states including thrombotic thrombocytopenic purpura, microvascular occlusion and atherosclerosis, due to the development of microvascular thrombi resulting from the complexation of the hyperactive vWF multimers and platelets at regions of low physiological shear.…”
Section: Implications In Physiology and Bioprocessingmentioning
confidence: 99%
“…25 In contrast, it has been shown that high shear-induced aggregation of washed platelets increases as a function of the concentration of exogenous purified vWF. 26 In addition, because wall shear rates of 3000 to 10 000 s Ϫ1 have been measured at the top of plaques, causing a 50% occlusion of the coronary arteries, 27 vWFGPIb binding may lead to arterial occlusion in a patient with atherosclerosis and precipitate a disease such as an ACS. It should therefore be possible to examine the association between the plasma vWF concentration and the vWF-GPIb interaction by blocking vWF binding to GPIb, where flow generates higher shear rates, to prevent ACSs.…”
Section: Discussionmentioning
confidence: 99%